Assessing construct validity of gen y acceptance on ‘3D’ industries and its determinant factors / Emy Noor Diana Zulkiflee, Fadilah Puteh and Jasmine Ahmad - Zulkiflee, Emy Noor Diana; Puteh, Fadilah; Ahmad, Jasmine (2021)
Malaysia is dependent on millions of foreign workers to fill up the job vacancies in the ‘dirty, dangerous and difficult’ (‘3D’) industries for the manufacturing, construction, services, plantation, and agriculture sectors (Ministry of Human Resources (MOHR), 2019). Due to the COVID-19 pandemic, the border control has restricted the movement of pass holders from India, Indonesia, and the Philippines, as well as a freeze on the recruitment of foreign workers (Immigration Department of Malaysia, 2020; Ministry of Human Resources, 2020). Globally, as of September 2021, the confirmed COVID-19 cases were about 218,946,836 with 1,786,004 cases reported in Malaysia (World Health Organisation (WHO), 2021). Therefore, worldwide issues on the pandemic have indirectly changed the recruiting trend in Malaysia, strategizing and prioritising the Malaysian locals, especially the Generation Y (Gen Y) youth over these unskilled foreign workers. Shrivastava, Ikonen, and Savolainen (2017), Nichols and Smith (2015), and Dries, Pepermans, and Carlier (2008) concurred that Gen Y referred to those who were born between 1980 to 2000. These unforeseen circumstances had in a way forced the employers and government to focus on the issues of unemployment amongst Malaysians. The latest unemployment rate as of June 2021 was 4.8%, and it kept increasing due to the COVID-19 pandemic (Department of Statistics Malaysia, 2021).